Interventions that use highly visual social media platforms to tackle unhealthy body image in adolescents and young adults: a systematic review protocol - Juan Carlos Bazo-Alvarez; Anthony Copez-Lonzoy; Janina Bazalar Palacios; Evelyn Goicochea-Ríos (BMJ Open)
Introduction Social media sites are increasingly used to assess and treat different mental health problems in adolescents and young adults. However, it is still unclear which social network sites are the most used for this purpose and what interventions for tackling unhealthy body image have been validated. This systematic review will assess evidence on the effectiveness of social media interventions in improving unhealthy body image among adolescents and young adults.Methods and analysis Five databases, including Embase, Scopus, MEDLINE, Web of Science (Core Collection) and PsycINFO, will be consulted, with a publication window starting in 2011 and ending on 31 October 2024. Rayyan software will detect and eliminate duplicates. We will include only studies based on social media-based interventions for adolescents and young adults with body image problems. Two independent reviewers will screen titles, abstracts and full-text articles, resolving conflicts through discussion with a third reviewer as needed. The two reviewers will complete the risk of bias assessments for each included study, using the Joanna Briggs Institute critical appraisal checklists for randomised controlled trials and quasi-experimental studies. We will report on the characteristics of studies, participants and interventions in descriptive narrative form, along with the results from the assessment of social media interventions.Ethics and dissemination Universidad Cesar Vallejo’s ethics committee approved this systematic review protocol as part of a wider project (code 100-CEI-EPM-UCV-2022). Results will be shared via social media to engage stakeholders and promote awareness of body image issues.